Application of SMART and TOPSIS in determining beneficiaries of latrine construction assistance - Apni Rahmadani Tanjung; M.Fakhriza; Aninda Muliani Harahap; Nur Sakinah Tanjung (Institute of Computer Science (IOCS), 2023)
In Bangun Raya Village there are still many people who defecate in the open (BABS) because they do not have latrines, resulting in an increase in disease transmission in Bangun Raya Village. To deal with this incident, the government of Bangun Raya Village provided assistance in building latrines to the less fortunate with predetermined criteria. However, the determination of beneficiaries for the construction of latrines is still based on manual calculations. The first thing the author did was to collect data from the poor family cards directly. To avoid mistakes in providing assistance for latrine construction, a decision support system is needed that can be used by the village apparatus in processing data. So that residents who receive assistance are residents who really need it and with the construction of a computerized decision support system, the decision making regarding the provision of latrine assistance can be more effective and efficient. By combining two methods, namely the SMART method as the stage for assessing the weight of the criteria data obtained and the stage for calculating the relative value of the assessment of weights and the TOPSIS method as the stage for normalizing the final result of calculating the relative value and the stage for ranking the results of normalization. The results of this study resulted in the Hilaluddin Harahap house in hamlet 2 being selected as the location for the construction of a 1st rank latrine with an accuracy value of 96% based on the desired criteria.